Social control of government policy through the citizen lawsuit mechanism - Paris Hendra Wijaya Sinaga; Firdausa Panji Bagas Wiratama; Fransiska Indriati; Dewi Ayu Rahayu; Sunarjo Sunarjo (Jurnal Cakrawala Hukum, 2022)
Social control is a form of monitoring whether or not a public policy is made from the planning and implementation stages in the community. Social control aims to prevent or treat so that the government does not set deviant actions or rules that can harm the community. So it is fitting for community groups to control and supervise the policies made by the government. However, it cannot be denied that there are still many policies that are made detrimental to the community and violate the public interest. This study analyzes inappropriate government policies in the community, using the empirical juridical method with a concept approach, a case approach, and a law approach. The results of this study indicate that several violations occurred due to government policies, so total control from the community is needed that can be carried out using a citizen lawsuit mechanism. The citizen lawsuit is the suitable lawsuit model to demand the Government evaluate and improve all efforts and policies to overcome problems detrimental to the community.How to cite item:Â Sinaga, P., Wiratama, F., Indriati, F., Rahayu, D., Sunarjo, S. (2022). Social control of government policy through the citizen lawsuit mechanism.Â Jurnal Cakrawala Hukum, 13(2), 123-134. DOI:https://doi.org/10.26905/idjch.v13i2.7875.